Early literacy and comprehension skills in children learning English as an additional language and monolingual children with language weaknesses - Bowyer-Crane, Claudine (Read Writ, 2016)
Many children learning English as an additional language (EAL) show reading comprehension difficulties despite adequate decoding. However, the relationship between early language and reading comprehension in this group is not fully understood. The language and literacy skills of 80 children learning English from diverse language backgrounds and 80 monolingual English-speaking peers with language weaknesses were assessed at school entry (mean age = 4 years, 7 months) and after 2 years of schooling in the UK (mean age = 6 years, 3 months). The EAL group showed weaker language skills and stronger word reading than the monolingual group but no difference in reading comprehension. Individual differences in reading comprehension were predicted by variations in decoding and language comprehension in both groups to a similar degree.